PENYULUHAN MASYARAKAT MELALUI PENGELOLAAN DESTINASI WISATA MATA AIR ALAMI TJIGIRANG DI DESA BOJONGLOA KECAMATAN BUAH DUA KABUPATEN SUMEDANG - Antonius Iskandar Yahya; Heri Sutardi; Eka Saputra; Rika Solihah; RD. Intan Media Ratna Puri (JURNAL PENGABDIAN MANDIRI, 2026)
This community service program aimed to enhance community capacity in managing the Tjigirang Natural Spring Tourism Destination in Bojongloa Village, Buahdua District, Sumedang Regency. The destination possesses considerable ecological, social, and economic potential; however, its development has been constrained by limited community knowledge regarding sustainable tourism management, environmental conservation, visitor services, and destination promotion. The program employed a participatory approach consisting of field observation, needs assessment, educational counseling, interactive discussions, mentoring, and evaluation. The target participants included village officials, tourism awareness groups (Pokdarwis), youth organizations, local micro and small enterprises, and community members. The results demonstrated improved community understanding of community-based tourism management, increased awareness of environmental conservation and cleanliness, enhanced knowledge of digital tourism promotion, and stronger community participation in destination development. Furthermore, the program strengthened collaboration among the village government, local communities, and higher education institutions, resulting in a shared commitment to sustainable tourism management and the formulation of a follow-up action plan. Overall, the program contributed to empowering the local community and establishing a foundation for sustainable tourism development that supports environmental preservation and local economic growth